PENDIDIKAN ISLAM BERWAWASAN LINGKUNGAN STUDI KASUS SMP 1 PARDASUKA - Ependi, Asip; Raba Pramodana, Dimas; Fadli, Ahmad Ilham; Murtadho, Ali; Baharudin; Ikhsan Mustofa (LP2M IAIN Sultan Amai Gorontalo, 2024)
The purpose of this research is to evaluate the effectiveness of the school environmental program in raising the awareness of students at SMP Negeri 1 Pardasuka about their environment. The background of this research is the importance of environmental awareness to anticipate environmental changes worldwide. The research method used is qualitative with data collection techniques through interviews with the Student Affairs Representative of SMP Negeri 1 Pardasuka and direct observation. The research results show that school environmental programs such as greening programs, hydroponics, and contextual learning effectively increase students' environmental awareness. The conclusion of this research is that school environmental programs need to be conducted sustainably and systematically to enhance students' environmental awareness. This research contributes to the development of effective and sustainable environmental education strategies.